Postmodernity, globalisation, communication and identity (Communicare: Journal for Communication Studies in Africa, 2022)
This article sets out to explore what it is to live in the postmodern age as an 'individual', that is,as someone with a distinct sense of self. Consideration is given both to the possibility that individualstoday, in the context of globalisation, may not have such a distinct sense of personal 'identity', andalso to what it is to have an identity. These questions are explored in relation to the so-calledpostmodern subject – or the subject in the age of globalisation, the age of hypercommunication,or of 'informatization' – which one may assume to be constituted very differently from the 'modern'subject of the 19th-century, or even more radically differently from premodern subjects. One couldsay that what Hardt and Negri regard as distinctive for postmodernity – informatisation, madepossible by advanced communications technology – is inseparable from the 'identity' of postmodernindividuals. Moreover, Derrida's insistence that the communications technology characteristic ofan era embodies a change in subjectivity (and hence, in identity), points to a significant clueregarding the identity of postmodern subjects. The aim of the present article is therefore to explorewhat all of these divergent considerations mean with regard to the issue of identity in thecontemporary world – whether one has reason to believe that identity has evaporated in the fluxof postmodern life, or if some of the theoretical perspectives invoked here enable one to affirmthe continued legitimacy of talking about identity today